Selective recrystallization of cellulose composite powders and microstructure creation through 3D binder jetting - Holland, Sonia; Tuck, Christopher; Foster, Tim (Elsevier, 2018)
Binder jetting is an additive manufacturing technique in which powdered material is sequentially laid down and printed on by an ink binder, in a selective manner, to form a 3D object. Unfortunately work in this area relevant to food materials is largely unpublished, however a typical application of this technique is sugar powder bound by a water and alcohol based ink with optional colour or flavour demonstrated by commercial ventures. In this work we demonstrate the use of a small scale powder layering device under an ink jet printer to test prototype powders prior to producing quantities typically used in commercially available binder jetting machines. Powders comprising predominantly of ball milled, amorphous cellulose were successfully used to create 3D structures when interacting polysaccharides were present in the ink (xanthan gum) and as a proportion of the powder component (glucomannan) by inducing selective recrystallization. These ingredients are categorized as dietary fibre, thus such formulations can be used to create low-calorie 3D printed food designs to be used within food products.